(untitled) (Bangladesh Journal of Medical Science, 2018)
Objective: To find out the situation and causes of anaemia in pregnant women at MMIMSR during the study period with special reference to the severity of the disease and to find out foetal outcome in pregnant women with anaemia. Methods: The study was conducted in Department of Obstetrics and Gynaecology, MMIMSR, Mullana, Ambala(India). The study was carried out between the period of october 2012 to September 2014.A total of 200 cases of moderate and severe anaemia were included in the study on the basis of simple random sampling method and 200 cases of non anaemic subjects were included to serve as controls for the anaemic group, during the study period. Hb gm/dl was taken as criteria for deciding anaemia cases and also to classify them according to the severity. Cases were classified according to WHO criteria. Results: Out of 200 cases of anaemia, 70% were moderately anaemic (Hb 7 – 9.9gm/dl) and 30% were severly anaemic (Hb < 7gm/dl). Microcytic hypochromic type of anaemia (82.5%) was more prevalent suggesting nutritional inadequacies as cause of anaemia. Adverse foetal outcome in the form of preterm birth (17%), still birth (3.5%), low birth weight babies (27.5%), neonatal morbidity (23.3%) was more in the anaemic group than non anaemic controls Conclusion: Anaemia in pregnancy has adverse foetal outcome in the form of decreased birth weight, increased perinatal morbidity and mortality. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.63-72